Natural Distribution, Regeneration and Growth Statistics of Poplars in Arunachal Pradesh - Beniwal, B. S.; Haridasan, K. (Indian Forester, 1992)
Populus ciliata and Populus gamblei are the two common poplars seen in Arunachal Pradesh. Their natural regeneration over the sub-tropical and temperate forests are very good. They come up well on exposed freshly turned soils, land slips, etc. They can be easily raised vegetatively by using branch cuttings and root suckers quick to establish, fast growing and profusely coppicing. All these characters suggests suitability in agroforestry, soil conservation and jhum reclamation work in Arunachal Pradesh for which there is a vast scope in the State.